(untitled) (Global Journal of Science Frontier Research, 2019)
The objective was to develop and implement a model of mixed integer programming (MIP) that numerically represented or simulated the optimum operating conditions of an integrated crop-livestock system with no-tillage (iCLS-NT), including animal transit. For the computational implementation of the model, we needed data on the fitness of the live weight gain of each animal of the considered herd, in each period and in each area of the iCLS-NT (confinement, pasture and annual crop), as well as marginal net income of each culture and costs per unit of the considered food. To test the validity of the developed mathematical model, we generated random values. To solve the problems, we used the MATLAB solver for mixed integer programming problems. Thus, after the computational implementation was carried out, we verified that the program satisfied all imposed constraints, maximized the weight gain of each animal, provided the best selection of annual crops and minimized the feed costs in the confinement area.